Kaiser Haq’s Reminiscence Poems: - Kazi Shahidul Islam (Crossings)
Bangladesh’s leading Anglophone poet Kaiser Haq is disenchanted with the ontology of history in its manifestations both as a site of contestations and miseries and as a potential tool serving the successive ruling class agenda. A veritable witness to the formative phases of the country’s overall development and, more importantly, a 1971 war veteran, he has formulated a poetics that engages less with the simplistic representations of history than with personal memory and subjectivity but that still opens windows into the historical timeline parallel to his maturation as an individual and, particularly, as an Anglophone poet. In an attempt to illustrate the inherent dialectic between memory and history in Haq’s poetry, this paper analyzes his lately composed reminiscence poems with reference to his prose pieces and interviews. It shows how the septuagenarian poet, through these poems, situates himself in the country’s evolving socio-cultural and politico-economic reality since the post-Partition times. Haq’s turn to memory is discernible in the correlation between his disillusionment about the state of affairs unfolding along the post-ideological axis and his late-life moral reflections on life. A corollary of this research is that these poems offer a retroactive understanding of Haq’s poetry within Bangladesh’s literary history.